The Implementation of Marriage Agreement Ratification by Notaries Post-Constitutional Court Decision 69/2015 Based on The Notary Law - Lisza Nurchayatie; KRA Michael Josef Widijatmoko; Radif Khotamir Rusli (Ann Publisher, 2025)
Background. The Indonesian Constitutional Court's Decision No. 69/PUU-XIII/2015 fundamentally reshaped the landscape of marital law by permitting post-nuptial agreements, a significant departure from the previous regime under Law No. 1 of 1974 on Marriage, which only recognized pre-nuptial contracts. This legal transformation introduced a dialectical tension between the principle of freedom of contract for spouses and the imperative to protect third-party creditor rights. Purpose. This article analyzes the juridical implications of this decision, focusing on the expanded role and heightened responsibility of Notaries in drafting and ratifying these agreements. Methods. Using a normative legal research method, this study examines the notary's obligations under Law No. 2 of 2014 on the Position of Notary (UUJN) to ensure the publicity principle is met, a condition essential to the binding effect of an agreement on third parties. The analysis of Supreme Court jurisprudence, particularly in bankruptcy cases, reveals an uncompromising stance on the requirement of timely registration as an absolute. Conclusion. The article concludes that while the Constitutional Court’s decision champions contractual autonomy, its practical implementation exposes notaries to significant liability risks, necessitating enhanced due diligence and systemic reforms such as a centralized digital registry. Implementation. A robust preventive professional framework to mitigate the risk of fraudulent conveyance and preserve legal certainty in commercial transactions.